2020
DOI: 10.1101/2020.04.28.065979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LPHN2 inhibits vascular permeability by differential control of endothelial cell adhesion

Abstract: Dynamic modulation of endothelial cell (EC) adhesion to extracellular matrix (ECM) in response to mechanostimuli is essential for blood vessel patterning and functioning. Yet, the molecular mechanisms involved in this biological process are far to be completely deciphered. Here, we identify the adhesion G protein-coupled receptor (ADGR) Latrophilin 2 (LPHN2) as a novel determinant of vascular morphogenesis and endothelial barrier function. In cultured ECs, endogenous LPHN2 localizes at ECM adhesions, signals t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Given the role of FLRT2 in modulating cortical migration during nervous system development, Akita et al proposed an analogous guidance function for FLRT2 in vascular development (Akita et al, 2016). FLRT2 is one of the primary ligands that binds and activates the adhesion G protein-coupled receptor LPHN2 , which acts as a repulsive guidance receptor that controls blood vessel structure and function in model systems (Camillo et al, 2021). FLRT2 has also been identified as an autoantigen, or cell-surface target, of anti-endothelial cell antibodies in the vascular systems of patients with systemic lupus erythematosus (Shirai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of FLRT2 in modulating cortical migration during nervous system development, Akita et al proposed an analogous guidance function for FLRT2 in vascular development (Akita et al, 2016). FLRT2 is one of the primary ligands that binds and activates the adhesion G protein-coupled receptor LPHN2 , which acts as a repulsive guidance receptor that controls blood vessel structure and function in model systems (Camillo et al, 2021). FLRT2 has also been identified as an autoantigen, or cell-surface target, of anti-endothelial cell antibodies in the vascular systems of patients with systemic lupus erythematosus (Shirai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…8A). ECM deposition is essential for mechanical support of vessels and guidance of cellular differentiation and functions ( 30 ). The ECM protein assembly and distribution in PHA/PEGDA-GDY scaffolds were similar to those of native vessels.…”
Section: Resultsmentioning
confidence: 99%
“…Mice lacking homophilic Flrt2 binding specifically in endothelial cells (Cdh5-Cre ERT2+ Flrt2 flox/R186N+D188T ; referred to hereafter as Flrt2 iΔEC/ΔFF ) showed suppression of tumor growth, angiogenesis, and hemorrhaging, similar to those in Flrt2 iΔEC mice (Figure 8C-E, N-Q). It should be noted that the FLRT2-latrophilins interaction (17,37,38) could account for this phenotype, in addition to its homophilic binding. A metastatic model based on AXT cells also showed that tumors in Flrt2 iΔEC/ΔFF demonstrated markedly lower levels of intravasation and metastasis than those in control mice (Figure 8F-M, R, S), suggesting that homophilic binding of Flrt2 provides the inter-endothelial adhesion required for maintenance of abnormalized vessels.…”
Section: Homophilic Binding Of Flrt2 Constitutes Tumor-specific Inter-endothelial Adhesionmentioning
confidence: 96%